Ergonomics intervention in steel panels handling for improving workers' well-being outcomes / Huck-Soo Loo … [et al.] - Huck-Soo Loo (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
The paper emphasizes an ergonomics intervention in a medium-sized manufacturing plant to fit jobs for workers with respect to the handling of steel panels for installation onto central station air handlers. Ergonomic risk factors were identified via qualitative and quantitative data obtained from general survey, participative assessments followed by direct observations. Ergonomics intervention by means of real life experiment was conducted. Post survey incorporating both direct observations and participative assessments was subsequently implemented to gauge its effectiveness. The intervention study comprises the introduction of a trolley designed for placing steel panels horizontally and a mobile rack created for upright placing of those panels. The action-oriented ergonomics study finally produced results which were in conformity with the research aim as anticipated.